Cutaneous sinus histiocytosis of face of the non-Langerhans cell histiocytoses type (cutaneous Rosai - Dorfman disease) - E. V. Sokolovsky; G. N. Mikheev; M. G. Rybakova; E. B. Manasheva; V. A. Seredina (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
An extremely rare case of sinus histiocytosis of the non-Langerhans cell histiocytoses type is described in 55-year-old patient with isolated localization of cutanious lesion on the right cheek without involvement of nodular structures. Main skin lesion was an erythematous-cyanotic node with multiple milia-like lesions on the top of it. Histologically revealed feature was a large number of plasma cells, besides phenomenon of emperipolesis was described, which was first falsely perceived by pathologists as phagocytosis. In immu-nohistochemistry assay the changes were characterized by proliferation of large polygonal histiocytes with accumulation of pentalamellar markers in its cytoplasm (protein S-100, CD68).